2017
DOI: 10.1002/slct.201602080
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity, the Hückel 4 n+2 Rule and Magnetic Current

Abstract: Quantum chemical calculations using density functional theory and correlated ab initio methods of the 10 π‐electron systems (N6H6)2+ and C2N4H6 show that the planar forms are no minima on the potential energy surfaces. The twisted ring structures of the two species are energy minima, but acyclic isomers are much lower in energy. The planar geometries sustain strong diamagnetic ring current comparable with that of benzene. In contrast, the calculated multicenter normalized Giambiagi electron delocalization inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
124
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(131 citation statements)
references
References 65 publications
7
124
0
Order By: Relevance
“….a multicenter delocalization is a necessary condition for a diatropic ring current to exist, provided that there are proper virtual molecular orbitals to excite to.''). [28][29][30][31][32] Finally, the DI-based indices (especially MCDI), unlike the aromaticity measures described above, enable one to study most of the types of aromaticity that can be found in literature. 6 Also, the MCDIs are the only descriptors that passed a set of rigorous tests for aromaticity quantifiers.…”
Section: Introductionmentioning
confidence: 99%
“….a multicenter delocalization is a necessary condition for a diatropic ring current to exist, provided that there are proper virtual molecular orbitals to excite to.''). [28][29][30][31][32] Finally, the DI-based indices (especially MCDI), unlike the aromaticity measures described above, enable one to study most of the types of aromaticity that can be found in literature. 6 Also, the MCDIs are the only descriptors that passed a set of rigorous tests for aromaticity quantifiers.…”
Section: Introductionmentioning
confidence: 99%
“…Available indices of aromaticity do not always give consistent results among themselves (Balaban, 1980; Lloyd, 1996; Poater et al, 2004; Zhao et al, 2017). Thus, for instance, predictions based on magnetic criteria of aromaticity often deviates from those based on energetic grounds (Aihara, 2006).…”
Section: Possible Solutions and Recommendationsmentioning
confidence: 99%
“…This latter group is peculiar, it is the only one that depends on the properties of a perturbed system. The electron distribution of the ground state of a system is significantly different from the magnetic perturbed one, because of this, the magnetic criteria for aromaticity has been recently criticized . However, these magnetic schemes have been widely used because they are based in a well‐known idea for chemist.…”
Section: Introductionmentioning
confidence: 99%
“…Even for a very symmetric carbocage, the current strength differs depending on which symmetry axis is chosen for the direction of B . It has also been reported that the high energy planar N 6 H 6 2+ has a similar current strength as benzene, which indicate that the ring currents parallel to the molecular plane do not possess all the electron delocalization information to discern between these two molecules. Another complication is that the analysis of the topology of a vector field, as J ( r ), is more cumbersome.…”
Section: Introductionmentioning
confidence: 99%